Chitosan-containing coating liquid, preparation method and application of chitosan-containing coating liquid in packaging material

By combining pre-oxidized dextran with carboxymethyl chitosan and filling with nano-metal particles, the problems of insufficient mechanical strength, water resistance and antibacterial properties of chitosan coating liquid in packaging materials are solved, achieving efficient oxygen barrier and long-term stability, which is suitable for food packaging materials.

CN120904730APending Publication Date: 2025-11-07SHANDONG RUNJIA PACKAGING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511125174.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-12
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Chitosan coating solutions have problems such as low mechanical strength, high brittleness, poor water resistance, limited antibacterial properties, and insufficient oxygen barrier properties in packaging materials. They are especially prone to swelling and failure in humid environments, and cannot meet the needs of food packaging.

Method used

A pre-oxidized dextran and carboxymethyl chitosan solution were used for composite modification. A dense three-dimensional network was constructed through Schiff base bonds and hydrogen bonds. Under microwave irradiation, nano-silver and nano-copper particles were formed, which enhanced the mechanical and antibacterial properties of the film and filled the gaps in the molecular chains to improve the oxygen barrier properties.

Benefits of technology

It significantly improves the mechanical strength and antibacterial durability of the film, broadens the antibacterial spectrum, enhances oxygen barrier properties, ensures long-term stability in humid environments, and meets the requirements of food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a chitosan-containing coating liquid, a preparation method and an application of the chitosan-containing coating liquid in a packaging material, and relates to the field of packaging materials. The preparation method of the chitosan-containing coating liquid comprises the following steps: carrying out composite modification; the composite modification method comprises the following steps: dropwise adding a pre-oxidized dextran solution into a carboxymethyl chitosan solution, and adjusting the pH value to 7; continuously stirring and dropwise adding the mixed precursor solution to obtain a mixed solution; and reacting the mixed solution in an intermittent microwave environment at 57-60 DEG C, centrifugally washing, and uniformly mixing and dispersing with deionized water and glycerol to obtain the chitosan-containing coating solution. According to the chitosan-containing coating liquid disclosed by the invention, the mechanical strength and brittleness of a film layer after the coating liquid is coated to form a film can be effectively improved; the problems that a film layer is poor in water resistance and easy to swell and lose efficacy in a water-containing environment or a humid environment are solved; the antibacterial spectrum of the film layer is further widened, and the antibacterial property, antibacterial durability and oxygen barrier property of the film layer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of packaging materials, in particular to a chitosan-containing coating liquid, a preparation method and application thereof in packaging materials. BACKGROUND

[0002] White pollution mainly refers to the pollution of natural environment caused by waste of traditional petroleum-based packaging materials, especially disposable plastic bags and plastic outer packaging. Plastic decomposes very slowly in nature and may take hundreds of years to completely degrade, which leads to the continuous accumulation of a large amount of plastic garbage in soil, rivers and oceans, and may release harmful substances during the decomposition process, further causing air pollution. Moreover, plastic pollution not only destroys the ecological environment, but also threatens wildlife, which may be poisoned or even die after eating or being entangled by plastic garbage.

[0003] Therefore, white pollution is an environmental problem that cannot be ignored in the process of industrialization, and poses a serious challenge to the ecological environment, human health and animal health. In order to reduce the impact of white pollution, it is necessary to develop degradable packaging materials. Emerging degradable packaging materials currently available include polysaccharide-based packaging materials, protein-based packaging materials, lactic acid-based packaging materials and other natural-based packaging materials. Natural-based packaging materials, as a sustainable alternative to petroleum-based materials, not only can share the resource pressure of petroleum-based packaging materials, but also can effectively improve the problems caused by the aforementioned white pollution.

[0004] Chitosan is a natural biological matrix macromolecular material, which is a linear polysaccharide composed of D-glucosamine (deacetylated unit) and N-acetylglucosamine (acetylated unit), and its precursor is chitin. Chitosan has the following advantages: (1) excellent biodegradability, no biological toxicity, and good biocompatibility; (2) chitosan molecules contain amino and hydroxyl groups, which are strong nucleophilic groups; (3) chitosan has good film-forming properties and certain antibacterial properties. Therefore, chitosan is widely used in agriculture, food, water treatment, medicine, cosmetics, fisheries, packaging and chemical industry and many other fields. In particular, in the field of degradable packaging materials, chitosan has been proven to be a natural degradable packaging material, but the special physicochemical properties of chitosan limit its application performance upper limit as a packaging material.

[0005] In the application of packaging materials, the coating liquid containing chitosan is coated and formed into a film, due to the large rigidity of the molecular chain of chitosan, the mechanical strength of the film layer is low, and the brittleness is large, the film layer is easy to break and crack in the use process of the packaging material, and the protective performance cannot be maintained. At the same time, due to the hydrophilicity of chitosan, water molecules can easily penetrate the film layer formed by the coating liquid containing chitosan, resulting in poor overall water resistance of the film layer, and the film layer has swelling failure problem in the water-containing environment or humid environment, and the long-term working stability is poor.

[0006] Further, since the antibacterial effect of chitosan is only through the positive charge to adsorb and destroy the cell membrane, the antibacterial effect on gram-negative bacteria, mold and the like is limited, and the antibacterial spectrum is narrow, and the antibacterial performance and antibacterial durability of the film layer need to be further improved. At the same time, due to the use demand of food packaging materials, the oxygen barrier performance of the film layer is required to be high, and the film layer needs to effectively block oxygen permeation and delay the oxidation and deterioration of food.

[0007] Therefore, the application provides a chitosan-containing coating liquid, a preparation method and application thereof in packaging materials, which can effectively improve the mechanical strength and brittleness of the film layer after the coating liquid is coated and formed into a film, overcome the problem that the film layer has poor water resistance and is easy to swell and fail in a water-containing environment or humid environment, and further broaden the antibacterial spectrum of the film layer, improve the antibacterial performance, antibacterial durability and oxygen barrier performance of the film layer, which has important technical significance and research value. SUMMARY

[0008] To solve the technical problems in the prior art, the application provides a preparation method of a chitosan-containing coating liquid, which can effectively improve the mechanical strength and brittleness of the film layer after the coating liquid is coated and formed into a film, overcome the problem that the film layer has poor water resistance and is easy to swell and fail in a water-containing environment or humid environment, and further broaden the antibacterial spectrum of the film layer, improve the antibacterial performance, antibacterial durability and oxygen barrier performance of the film layer. The application also provides a chitosan-containing coating liquid prepared by the foregoing method, and application of the chitosan-containing coating liquid in packaging materials.

[0009] To solve the above technical problems, the technical solutions adopted by the application are as follows: A preparation method of a chitosan-containing coating liquid, comprising the following steps: composite modification. The method for the composite modification is that the pre-oxidized dextran solution is added dropwise into the carboxymethyl chitosan solution under stirring, and the pH is adjusted to 7 after the dropwise addition is completed; the mixed precursor solution is continuously added dropwise under stirring, and is uniformly mixed after the dropwise addition is completed to obtain a mixed solution; the mixed solution is reacted at 57-60°C in an intermittent microwave environment, and is placed in an ice bath to obtain a microwave reaction solution; the microwave reaction solution is centrifuged to remove supernatant to obtain a centrifugate; the centrifugate is washed by centrifugation, and is uniformly dispersed with deionized water and glycerol to prepare a coating solution containing chitosan with a solid content of 1.8-1.9 wt%. The mixed precursor solution is a mixed aqueous solution of silver nitrate and copper nitrate.

[0010] Preferably, the concentration of the carboxymethyl chitosan solution is 1.2-1.3 wt%. The pre-oxidized dextran solution is an aqueous solution of pre-oxidized dextran with an oxidation degree of 27-30%, and the concentration is 1-1.2 wt%. The concentration of silver nitrate in the mixed precursor solution is 0.3-0.33 mol / L, and the concentration of copper nitrate is 0.1-0.11 mol / L.

[0011] Preferably, the volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution is 1:1-1.1. The volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution is 1:24-25. The added weight of glycerol is 17-19% of the total dry weight of carboxymethyl chitosan and pre-oxidized dextran.

[0012] Preferably, the dropwise addition time of the mixed precursor solution is 40-50 min. The reaction time of the mixed solution in the intermittent microwave environment at 57-60°C is 4-6 min, and the microwave power is 500-550 W.

[0013] Further, the preparation method further includes the following steps: pre-oxidation treatment. The method for the pre-oxidation treatment is that the dextran T40 is put into deionized water under room temperature conditions, and the NaIO4 solution is added dropwise under stirring in a light-proof environment after uniform mixing; the dropwise addition is completed, and the reaction is continued under stirring to obtain a reaction solution; the reaction solution is dialyzed and freeze-dried to prepare the pre-oxidized dextran.

[0014] Preferably, the weight ratio of the dextran T40 to the deionized water is 1:20-25. The molar ratio of the dextran T40 to NaIO4 in the NaIO4 solution is 1:1.1-1.2. The concentration of the NaIO4 solution is 0.45-0.5 mol / L.

[0015] Preferably, the dropping speed of the NaIO4 solution is 0.4-0.6 mL / min; The stirring reaction time after the dropping of the NaIO4 solution is completed is 4-5 h; The molecular weight cut-off of the dialysis is 12-14 KDa, and the dialysis time is 24-30 h.

[0016] A chitosan-containing coating liquid prepared by the preparation method.

[0017] The application of the aforementioned chitosan-containing coating liquid in packaging materials, wherein the chitosan-containing coating liquid is coated onto the surface of a cellulose base paper, the wet film thickness of the coating is controlled to be 160-170 μm, and the coating is dried after completion to prepare the packaging materials.

[0018] Further, in the coating process, the coating speed is controlled to be 12-15 m / min; The drying is performed in a temperature environment of 55-58 ℃, under the condition that the hot air speed is 10-10.5 m / s, and the first-stage hot air drying is performed for 40-50 s; then the drying is performed in a temperature environment of 63-65 ℃, under the condition that the hot air speed is 8-8.5 m / s, and the second-stage hot air drying is performed for 55-60 s; then the drying is performed in a temperature environment of 45-48 ℃, under the condition that the hot air speed is 5-5.5 m / s, and the third-stage hot air drying is performed for 45-50 s, to complete the drying.

[0019] Compared with the prior art, the present application has the following beneficial effects: (1) The preparation method of the chitosan-containing coating liquid of the present application comprises the following steps: mixing a pre-oxidized dextran solution and a carboxymethyl chitosan solution, dropping the mixture into a mixed precursor solution containing silver nitrate and copper nitrate to obtain a mixed solution, mixing the mixed solution with deionized water and glycerol after reaction in an intermittent microwave environment to obtain the chitosan-containing coating liquid; wherein the amino group of the carboxymethyl chitosan and the aldehyde group of the pre-oxidized dextran are covalently crosslinked by forming a Schiff base bond, and the hydroxyl groups exposed by the molecular chain breakage in the pre-oxidized dextran form a dense hydrogen bond network with the carboxymethyl chitosan, thereby enhancing the intermolecular connection and constructing a compact three-dimensional network; at the same time, the aldehyde group of the pre-oxidized dextran reduces metal ions (Ag + , Cu 2+After the nano-silver particles and the nano-copper particles, on the one hand, the carboxyl groups of the carboxymethyl chitosan are chelated with the nano-particles through ionic bonds; on the other hand, the carboxymethyl chitosan and the pre-oxidized dextran form a three-dimensional cross-linked network to coat the nano-silver particles and the nano-copper particles, and the nano-particles fill the gaps of the molecular chains to form a carboxymethyl chitosan-pre-oxidized dextran-nano-silver / nano-copper composite system; the above technical means cooperate with each other and have a synergistic effect, which can effectively improve the mechanical strength and brittleness of the film layer after the coating liquid is coated and formed into a film; the problem that the film layer has poor water resistance and is easy to swell and fail in a water-containing environment or a humid environment is overcome; and the antibacterial spectrum of the film layer is further widened, and the antibacterial performance, antibacterial durability and oxygen barrier performance of the film layer are improved.

[0020] (2) After detection, the tensile strength of the film layer formed by using the coating liquid containing chitosan according to the application is 55.0-55.6 MPa, the elongation at break is 44.7-45.2%, and the peeling strength is 1.8-1.9 N / mm; after the film layer is soaked in constant-temperature deionized water at 25℃ for 24h, the weight gain rate of the film layer is 18.9-19.6%, and the thickness increase rate is 9.7-10.2%.

[0021] (3) After detection, the packaging material coated with the coating liquid containing chitosan prepared by using the coating liquid containing chitosan according to the application has an antibacterial rate of 99.8-99.9% on Staphylococcus aureus, an antibacterial rate of 99.6-99.8% on Escherichia coli, and an antibacterial rate of 99.7-99.8% on Klebsiella pneumoniae; the mildew-proof grade on Aspergillus niger, Aspergillus terreus and Paecilomyces variotii is all 0 grade (no mold growth is observed under 50 times magnification of a microscope).

[0022] (4) After detection, the packaging material coated with the coating liquid containing chitosan prepared by using the coating liquid containing chitosan according to the application has an oxygen transmission rate of 8.5-8.8 cm 3 / m 2 ·day; after the packaging material is placed in an environment with a temperature of 40℃ and a relative humidity of 70% for 15 days, the oxygen transmission rate is 8.9-9.2 cm 3 / m 2 ·day.

[0023] (5) After detection, the packaging material coated with the coating liquid containing chitosan prepared by using the coating liquid containing chitosan according to the application has a tensile strength of 53.9 MPa and a peeling strength of 1.8 N / mm after being placed in an environment with a temperature of 55℃ and a relative humidity of 90% for 10 days; the antibacterial rate on Staphylococcus aureus is 99.5%, the antibacterial rate on Escherichia coli is 99.3%, and the antibacterial rate on Klebsiella pneumoniae is 99.4%. DETAILED DESCRIPTION

[0024] For a more clear understanding of the technical features, objectives and effects of the present application, the specific embodiments of the present application are described. It should be noted that the following detailed description is exemplary and is intended to provide further description of the present application. Unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as generally understood by those skilled in the art to which the present application belongs.

[0025] It should be noted that the terms used herein are only for the purpose of describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. As used herein, "first", "second", etc. are used to distinguish similar objects, and are not intended to describe a specific order or sequence, and it should also be understood that when the terms "comprise" and / or "include" are used in the specification, there is a feature, step, operation, device, component and / or combination thereof.

[0026] The present application provides a preparation method of a chitosan-containing coating liquid, comprising the following steps: composite modification; The method for composite modification is that the pre-oxidized dextran solution is added dropwise into the carboxymethyl chitosan solution under stirring, and the pH is adjusted to 7 after the dropwise addition is completed; the mixed precursor solution is continuously added dropwise under stirring, and is uniformly mixed after the dropwise addition is completed to obtain a mixed solution; the mixed solution is reacted at 57-60℃ in an intermittent microwave environment, and is placed in an ice bath to obtain a microwave reaction solution; the microwave reaction solution is centrifuged to remove the supernatant to obtain a centrifugate; the centrifugate is washed by centrifugation, and is uniformly mixed and dispersed with deionized water and glycerol to prepare a chitosan-containing coating liquid with a solid content of 1.8-1.9wt%. The mixed precursor solution is a mixed aqueous solution of silver nitrate and copper nitrate.

[0027] The present application adopts the method that the pre-oxidized dextran solution is mixed with the carboxymethyl chitosan solution, and then is added dropwise into the mixed precursor solution containing silver nitrate and copper nitrate to obtain a mixed solution; the mixed solution is reacted in an intermittent microwave environment, and is mixed with deionized water and glycerol to prepare a chitosan-containing coating liquid; wherein the amino group of the carboxymethyl chitosan and the aldehyde group of the pre-oxidized dextran are covalently cross-linked by forming a Schiff base bond, and the hydroxyl groups exposed by the molecular chain breakage in the pre-oxidized dextran form a dense hydrogen bond network with the carboxymethyl chitosan to enhance the intermolecular connection and construct a compact three-dimensional network; at the same time, the aldehyde group of the pre-oxidized dextran reduces metal ions (Ag + , Cu 2+ ) into nano silver particles and nano copper particles under the action of microwave thermal effect, on the one hand, the carboxyl group of the carboxymethyl chitosan chelates the nano particles through ionic bonds; on the other hand, the three-dimensional cross-linked network formed by the carboxymethyl chitosan and the pre-oxidized dextran coats the nano silver particles and nano copper particles, and fills the molecular chain gap by the nano particles to form a carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system.

[0028] The carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system is formed by the aforementioned Schiff base covalent bond, the dense hydrogen bond network formed by the hydroxyl groups in the aforementioned pre-oxidized dextran and the carboxymethyl chitosan, the compact three-dimensional network formed by the aforementioned Schiff base covalent bond, and the filling of the nano silver and nano copper particles to the molecular chain gap, which jointly act on the dispersed stress, improve the mechanical properties of the film layer formed by the coating solution of the composite system, overcome the brittleness defect of the film layer formed by the traditional chitosan coating solution, and improve the flexibility and tear resistance of the film layer by the dextran, and optimize the tensile strength of the film layer.

[0029] Further, the Schiff base bond formed by the amino group of the carboxymethyl chitosan and the aldehyde group of the pre-oxidized dextran can replace the original hydrophilic group, and the nano silver and nano copper particles can fill the molecular chain gap of the carboxymethyl chitosan / pre-oxidized dextran, improve the water resistance of the film layer formed by the coating solution of the composite system, avoid the swelling failure of the film layer in the water-containing environment or humid environment, and further improve the long-term working stability.

[0030] Further, the carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system further expands the antibacterial spectrum and improves the antibacterial performance of the film layer by destroying the cell membrane of gram-negative bacteria or gram-positive bacteria through the nano silver, infecting the DNA replication, and the inhibition of the nano copper on the mold, which can effectively inhibit the gram-positive bacteria, gram-negative bacteria and mold.

[0031] Further, the carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system effectively blocks the oxygen permeation by the dense crosslinking of carboxymethyl chitosan and pre-oxidized dextran, and the filling of the nano silver and nano copper particles to the molecular chain gap of carboxymethyl chitosan / pre-oxidized dextran, which further improves the oxygen barrier performance of the film layer; at the same time, the film layer is endowed with certain antioxidant performance by the free radical scavenging performance of chitosan and pre-oxidized dextran, and the quenching effect of nano metal ions on free radicals, which further improves the long-term working stability of the film layer.

[0032] In the embodiment of the present application, the concentration of the carboxymethyl chitosan solution is 1.2-1.3wt%; the pre-oxidized dextran solution is an aqueous solution of pre-oxidized dextran with an oxidation degree of 27-30%, and the concentration is 1-1.2wt%; the concentration of silver nitrate in the mixed precursor solution is 0.3-0.33mol / L, and the concentration of copper nitrate is 0.1-0.11mol / L. Among them, by controlling the oxidation degree of the pre-oxidized dextran to be 27-30%, the molecular chain of the pre-oxidized dextran is prevented from being excessively broken, thereby avoiding the reduction of the cross-linking effect of the pre-oxidized dextran and the carboxymethyl chitosan, and avoiding the reduction of the improvement effect of the pre-oxidized dextran on the mechanical properties of the film layer; and by controlling the pre-oxidized dextran with a specific oxidation degree, the pre-oxidized dextran is promoted to accommodate and coat the nano-metal particles. Further, by combining silver nitrate and copper nitrate in the mixed precursor solution and controlling the concentration thereof, the aforementioned technical effects are achieved while avoiding the adverse effect of copper ions on the color of the film layer.

[0033] In the embodiment of the present application, the volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution is 1:1-1.1; the volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution is 1:24-25; and the added weight of glycerol is 17-19% of the total dry weight of the carboxymethyl chitosan and the pre-oxidized dextran.

[0034] In the embodiment of the present application, the dropping time of the mixed precursor solution is 40-50min; the reaction time of the mixed solution in the intermittent microwave environment is 4-6min at 57-60℃, and the microwave power is 500-550W. Among them, by controlling the slow dropping of the mixed precursor solution, the local concentration in the mixing process is prevented from being too high, and the agglomeration of nano-metal particles in the subsequent microwave reaction is avoided, and the subsequent microwave reaction is ensured to be effectively carried out on the basis of sufficient mixing.

[0035] In the embodiment of the present application, the preparation method further comprises the following steps: pre-oxidation treatment; the method of the pre-oxidation treatment is that, under room temperature conditions, dextran T40 is put into deionized water, and after being uniformly mixed, NaIO4 solution is added dropwise under light-proof environment while stirring; after the dropping is completed, the reaction is continued to obtain a reaction liquid; the reaction liquid is dialyzed and freeze-dried to obtain pre-oxidized dextran. Among them, by the oxidation of NaIO4 on dextran T40, the oxidation degree of the pre-oxidized dextran is controlled to be 27-30%, the molecular chain of the pre-oxidized dextran is prevented from being excessively broken, thereby avoiding the reduction of the cross-linking effect of the pre-oxidized dextran and the carboxymethyl chitosan, and avoiding the reduction of the improvement effect of the pre-oxidized dextran on the mechanical properties of the film layer; and by controlling the pre-oxidized dextran with a specific oxidation degree, the pre-oxidized dextran is promoted to accommodate and coat the nano-metal particles.

[0036] In the embodiment of the present application, the weight ratio of the dextran T40 to deionized water is 1:20-25; the molar ratio of the dextran T40 to NaIO4 in the NaIO4 solution is 1:1.1-1.2; and the concentration of the NaIO4 solution is 0.45-0.5 mol / L.

[0037] In the embodiment of the present application, the dropping speed of the NaIO4 solution is 0.4-0.6 mL / min; the stirring reaction time after the dropping of the NaIO4 solution is completed is 4-5 h; and the molecular weight cut-off of the dialysis is 12-14 KDa, and the dialysis time is 24-30 h.

[0038] The embodiment of the present application also provides a chitosan-containing coating solution prepared by the method.

[0039] The embodiment of the present application also provides application of the chitosan-containing coating solution in a packaging material, wherein the chitosan-containing coating solution is coated onto the surface of a cellulose base paper, the wet film thickness of the coating is controlled to be 160-170 μm, and the coating is dried after the coating is completed to obtain the packaging material.

[0040] In the embodiment of the present application, the coating speed is controlled to be 12-15 m / min during the coating process. The drying is carried out in a temperature environment of 55-58 ℃, under the condition that the hot air speed is 10-10.5 m / s, and the first-stage hot air drying is carried out for 40-50 s; then the drying is carried out in a temperature environment of 63-65 ℃, under the condition that the hot air speed is 8-8.5 m / s, and the second-stage hot air drying is carried out for 55-60 s; and then the drying is carried out in a temperature environment of 45-48 ℃, under the condition that the hot air speed is 5-5.5 m / s, and the third-stage hot air drying is carried out for 45-50 s to complete the drying. In the first-stage hot air drying process, the water evaporation on the surface of the wet film is adjusted by the predetermined process parameters to quickly remove the free water on the surface and avoid the film layer from cracking; in the second-stage hot air drying process, the combined water is deeply dried and evaporated, and the film layer is further solidified; and in the third-stage hot air drying process, the drying process is consolidated to prevent the film layer from warping and release the stress of the film layer.

[0041] The present application will be further described below in combination with some specific embodiments.

[0042] Embodiment 1 The present embodiment provides a preparation method of a chitosan-containing coating solution, and the specific method is as follows: 1. Pre-oxidation treatment Dextran-40 was put into 20 times weight of deionized water at room temperature, stirred for 20 min, and then a 0.45 mol / L NaIO4 solution was added dropwise at a rate of 0.4 mL / min under stirring at 250 rpm in the dark; after the dropwise addition of the NaIO4 solution was completed, the reaction was continued for 4 h under stirring, and then the reaction was quenched by adding ethylene glycol to obtain a reaction solution; the reaction solution was placed in a dialysis bag with a molecular weight cut-off of 14 KDa, and dialysis purification was performed in a nitrogen environment for 30 h, with the water being changed every 5 h during the dialysis purification; after the dialysis purification was completed, the dialysis bag was placed in a freeze-drying device, and freeze-drying was performed to obtain pre-oxidized dextran with an oxidation degree of 27.2% (determined by hydroxylamine hydrochloride titration), which was stored for later use.

[0043] The molar ratio of Dextran-40 to NaIO4 in the NaIO4 solution was 1:1.1.

[0044] 2. Compound modification ①Carboxymethyl chitosan was put into deionized water, stirred at 40°C until completely dissolved to obtain a 1.2 wt% carboxymethyl chitosan solution, which was stored for later use; pre-oxidized dextran was put into deionized water, stirred at room temperature for 20 min to obtain a 1 wt% pre-oxidized dextran solution, which was stored for later use; under stirring at 400 rpm, the pre-oxidized dextran solution was added dropwise into the carboxymethyl chitosan solution, and after the dropwise addition was completed, the pH was adjusted to 7 using a 0.1 mol / L sodium hydroxide solution; the dropwise addition of the mixed precursor solution was continued, and the dropwise addition time of the mixed precursor solution was controlled to be 40 min; after the dropwise addition was completed, stirring was continued for 10 min to obtain a mixed solution.

[0045] The volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution was 1:1.

[0046] The mixed precursor solution was a mixed aqueous solution of silver nitrate and copper nitrate; the concentration of silver nitrate in the mixed precursor solution was 0.3 mol / L, and the concentration of copper nitrate was 0.1 mol / L.

[0047] The volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution was 1:24.

[0048] ②The mixed solution was placed in an intermittent microwave reaction device, the microwave power was set to 500 W, and the reaction temperature was maintained at 57°C by intermittent microwave irradiation, and the reaction time was 6 min; after the reaction was completed, the mixture was placed in an ice bath in the dark for 10 min to obtain a microwave reaction solution; after centrifugal separation at 11000 rpm for 20 min, the supernatant was discarded to obtain a centrifugate; after the centrifugate was washed with deionized water by centrifugation and uniformly dispersed with deionized water and glycerol by ultrasonic dispersion, a coating solution containing chitosan with a solid content of 1.85 wt% was prepared.

[0049] The added weight of glycerol is 17.5% of the total weight of the carboxymethyl chitosan and the pre-oxidized dextran.

[0050] The present embodiment also provides a chitosan-containing coating solution prepared by the aforementioned method.

[0051] Embodiment 2 The present embodiment provides a method for preparing a chitosan-containing coating solution, and the specific method is as follows: 1. Pre-oxidation treatment At room temperature, Dextran-40 was added to 22 times the weight of deionized water, stirred for 25 min, and then a 0.47 mol / L NaIO4 solution was added dropwise at a rate of 0.5 mL / min under stirring at 280 rpm in the dark. After the dropwise addition of the NaIO4 solution was completed, the stirring was continued for 4.5 h, and then the reaction was quenched by adding ethylene glycol. The reaction solution was then placed in a dialysis bag with a molecular weight cut-off of 14 KDa and dialyzed for 30 h in a nitrogen environment. The dialysis solution was changed every 5 h during the dialysis. After the dialysis was completed, the dialysis bag was placed in a freeze-drying device, and the pre-oxidized dextran with an oxidation degree of 29.0% (determined by hydroxylamine hydrochloride titration) was obtained by freeze-drying.

[0052] The molar ratio of Dextran-40 to NaIO4 in the NaIO4 solution is 1:1.15.

[0053] 2. Complex modification ①Carboxymethyl chitosan was added to deionized water and stirred at 42°C until completely dissolved to obtain a 1.25 wt% carboxymethyl chitosan solution, which was used as needed. The pre-oxidized dextran was added to deionized water and stirred at room temperature for 25 min to obtain a 1.1 wt% pre-oxidized dextran solution, which was used as needed. Under stirring at 450 rpm, the pre-oxidized dextran solution was added to the carboxymethyl chitosan solution, and after the addition was completed, the pH was adjusted to 7 using a 0.1 mol / L sodium hydroxide solution. The mixed precursor solution was continuously added and stirred for 15 min to obtain a mixed solution.

[0054] The volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution is 1:1.05.

[0055] The mixed precursor solution is a mixed aqueous solution of silver nitrate and copper nitrate. The concentration of silver nitrate in the mixed precursor solution is 0.33 mol / L, and the concentration of copper nitrate is 0.11 mol / L.

[0056] The volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution is 1:24.5.

[0057] The mixture is placed in an intermittent microwave reaction device, the microwave power is set to 530 W, the reaction temperature is maintained at 58°C through intermittent microwave irradiation, the reaction time is 5 min, after the reaction is completed, the mixture is placed in dark for 15 min in an ice bath, and a microwave reaction solution is obtained; after centrifugal separation at 12000 rpm for 20 min, the supernatant is discarded, and a centrifugate is obtained; the centrifugate is washed by centrifugal separation with deionized water, and then is uniformly dispersed with deionized water and glycerol to prepare a coating solution containing chitosan with a solid content of 1.85 wt%.

[0058] The added weight of glycerol is 17.5% of the total weight of the carboxymethyl chitosan and the pre-oxidized dextran.

[0059] The embodiment also provides the coating solution containing chitosan prepared by the foregoing method.

[0060] Example 3 The embodiment provides a preparation method of a coating solution containing chitosan, and the specific method is as follows: 1. Pre-oxidation treatment At room temperature, dextran T40 is added into 25 times weight of deionized water, stirred for 30 min, and then 0.5 mol / L NaIO4 solution is added dropwise at a dropwise rate of 0.6 mL / min under light shielding at 300 rpm; after the dropwise addition of the NaIO4 solution is completed, the stirring reaction is continued for 5 h, and ethylene glycol is added to quench the reaction, to obtain a reaction solution; the reaction solution is placed in a dialysis bag with a molecular weight cut-off of 14 KDa, and dialysis purification is performed in a nitrogen environment for 30 h, and the water is changed every 5 h during the dialysis purification; after the dialysis purification is completed, the physical in the dialysis bag is placed in a freeze-drying device, and freeze-drying is performed to prepare pre-oxidized dextran with an oxidation degree of 29.8% (determined by hydroxylamine hydrochloride titration method), which is stored for use.

[0061] The molar ratio of dextran T40 to NaIO4 in the NaIO4 solution is 1:1.2.

[0062] 2. Compound modification ①Carboxymethyl chitosan was put into deionized water, and stirred at 45℃ until completely dissolved to obtain a carboxymethyl chitosan solution with a concentration of 1.3wt%, which was ready for use; pre-oxidized dextran was put into deionized water, and stirred at room temperature for 30min to obtain a pre-oxidized dextran solution with a concentration of 1.2wt%, which was ready for use; the pre-oxidized dextran solution was added dropwise into the carboxymethyl chitosan solution under the condition of stirring at 500rpm, and after the dropwise addition was completed, the pH was adjusted to 7 using a sodium hydroxide solution with a concentration of 0.1mol / L; the mixed precursor solution was continuously added dropwise under stirring, and the dropwise addition time of the mixed precursor solution was controlled to be 50min, and after the dropwise addition was completed, stirring was continued for 20min to obtain a mixed solution.

[0063] The volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution was 1:1.1.

[0064] The mixed precursor solution was an aqueous mixed solution of silver nitrate and copper nitrate; the concentration of silver nitrate in the mixed precursor solution was 0.32mol / L, and the concentration of copper nitrate was 0.11mol / L.

[0065] The volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution was 1:25.

[0066] ②The mixed solution was placed in an intermittent microwave reaction device, the microwave power was set to 550W, the reaction temperature was maintained at 60℃ through intermittent microwave irradiation, the reaction time was 4min, after the reaction was completed, the reaction solution was placed in an ice bath in the dark for 20min to obtain a microwave reaction solution; after centrifugal separation at 12000rpm for 20min, the supernatant was discarded to obtain a centrifugate; the centrifugate was uniformly dispersed with deionized water and glycerol through ultrasonic dispersion after being washed with deionized water through centrifugation to obtain a coating liquid containing chitosan with a solid content of 1.85wt%.

[0067] The added weight of glycerol was 17.5% of the total dry weight of carboxymethyl chitosan and pre-oxidized dextran.

[0068] The embodiment also provides a coating liquid containing chitosan prepared by the aforementioned method.

[0069] Example 4 The embodiment provides an application of the aforementioned coating liquid containing chitosan in packaging materials, and the specific method is as follows: The coating liquid containing chitosan is coated onto the surface of the cellulose base paper in a manner of doctor blade coating, the wet film thickness of the coating liquid containing chitosan on the surface of the cellulose base paper is controlled to be 165 μm in the process of doctor blade coating, and the coating speed is 12 m / min; after the coating is completed, the cellulose base paper coated with the wet film is subjected to three-stage hot air drying, specifically, the cellulose base paper coated with the wet film is subjected to first-stage hot air drying for 50 s at a temperature environment of 55 ℃ and under the condition of a hot air speed of 10 m / s; then subjected to second-stage hot air drying for 60 s at a temperature environment of 63 ℃ and under the condition of a hot air speed of 8 m / s; and then subjected to third-stage hot air drying for 50 s at a temperature environment of 45 ℃ and under the condition of a hot air speed of 5 m / s, to obtain the packaging material coated with the coating liquid containing chitosan.

[0070] Example 5 The application of the aforementioned coating liquid containing chitosan in packaging materials is provided in this example, and the specific method is as follows: The coating liquid containing chitosan is coated onto the surface of the cellulose base paper in a manner of doctor blade coating, the wet film thickness of the coating liquid containing chitosan on the surface of the cellulose base paper is controlled to be 165 μm in the process of doctor blade coating, and the coating speed is 13.5 m / min; after the coating is completed, the cellulose base paper coated with the wet film is subjected to three-stage hot air drying, specifically, the cellulose base paper coated with the wet film is subjected to first-stage hot air drying for 45 s at a temperature environment of 56 ℃ and under the condition of a hot air speed of 10.2 m / s; then subjected to second-stage hot air drying for 58 s at a temperature environment of 64 ℃ and under the condition of a hot air speed of 8.2 m / s; and then subjected to third-stage hot air drying for 48 s at a temperature environment of 46 ℃ and under the condition of a hot air speed of 5.2 m / s, to obtain the packaging material coated with the coating liquid containing chitosan.

[0071] Example 6 The application of the aforementioned coating liquid containing chitosan in packaging materials is provided in this example, and the specific method is as follows: The coating liquid containing chitosan is coated onto the surface of the cellulose base paper in a manner of doctor blade coating, the wet film thickness of the coating liquid containing chitosan on the surface of the cellulose base paper is controlled to be 165 μm in the process of doctor blade coating, and the coating speed is 15 m / min; after the coating is completed, the cellulose base paper coated with the wet film is subjected to three-stage hot air drying, specifically, the cellulose base paper coated with the wet film is subjected to first-stage hot air drying for 40 s at a temperature environment of 58 ℃ and under the condition of a hot air speed of 10.5 m / s; then subjected to second-stage hot air drying for 55 s at a temperature environment of 65 ℃ and under the condition of a hot air speed of 8.5 m / s; and then subjected to third-stage hot air drying for 45 s at a temperature environment of 48 ℃ and under the condition of a hot air speed of 5.5 m / s, to obtain the packaging material coated with the coating liquid containing chitosan.

[0072] Comparative Example 1 The preparation method of the chitosan-containing coating solution of Comparative Example 1 adopts the technical solution of Example 2, which is different in that: 1) in the composite modification, dextran T40 is used instead of pre-oxidized dextran; 2) in the mixed precursor solution, the addition of copper nitrate is omitted.

[0073] According to the application method described in Example 5, the coating solutions of Examples 1-3 and Comparative Example 1 are respectively used to coat the cellulose base paper, and the packaging materials coated with the chitosan-containing coating solution are obtained correspondingly; the tensile strength, elongation at break and peel strength of the film layer of each packaging material are detected for the mechanical properties of the film layer formed by each coating solution. Among them, the detection of tensile strength and elongation at break is carried out by a universal material testing machine, and the specific method is referred to ASTM D882 "Standard Test Methods for Tensile Properties of Plastics Thin and Sheet"; the detection of peel strength is carried out by a peel testing machine, and the specific method is referred to ASTM D903 "Standard Test Methods for Adhesive Bond Peel Resistance or Tensile Strength of Bonded Joints". The specific results are shown in the following table:

[0074] Further, for the water resistance of the film layer formed by each coating solution, according to the application method described in Example 5, the coating solutions of Examples 1-3 and Comparative Example 1 are respectively used to coat the base body (siliconized glass plate) to form a film layer, and then the film layer material is peeled off; the water absorption rate and the swelling rate of each film layer are detected. Among them, the detection of water absorption rate is to place the same mass of film layer in constant temperature deionized water at 25°C, soak for 24h, and then calculate the weight gain rate of the film layer according to the initial weight of the film layer. The specific method is referred to GB / T 1034-2008 "Determination of Water Absorption of Plastics". The detection of swelling rate is to place the film layer in constant temperature deionized water at 25°C, soak for 24h, and then calculate the thickness increase rate according to the initial thickness of the film layer. The specific results are shown in the following table:

[0075] Further, for the antibacterial properties of the film layer formed by each coating solution, the coating solutions of Examples 1-3 and Comparative Example 1 are respectively used to coat the cellulose base paper, and the packaging materials coated with the chitosan-containing coating solution are obtained correspondingly; according to the relevant methods of GB / T 21866-2008 "Determination of Antibacterial Property of Antibacterial Coatings (Paint Film) and Antibacterial Effect", the antibacterial rates of Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae are detected; and according to the relevant methods of HG / T3950-2007 "Antibacterial Coatings", the mildew resistance grades of Aspergillus niger, Aspergillus terreus and Paecilomyces variotii are detected. The specific results are shown in the following table:

[0076] Further, the oxygen barrier properties of the film layers formed by the coating solutions were tested. The cellulose base paper was coated with the coating solutions of Examples 1-3 and Comparative Example 1 according to the application method described in Example 5 to obtain the packaging materials coated with the coating solutions containing chitosan. The oxygen permeation amount per unit area per unit time of each packaging material was detected using a Y110 oxygen permeation analyzer (pressure difference method) in an environment with a temperature of 25°C and a relative humidity of 50%. Meanwhile, each packaging material was placed in an environment with a temperature of 40°C and a relative humidity of 70% for 15 days, and then the oxygen permeation amount of each packaging material was detected according to the foregoing method. The specific results are shown in the following table:

[0077] Further, the cellulose base paper was coated with the coating solutions of Example 2 and Comparative Example 1 according to the application method described in Example 5 to obtain the packaging materials coated with the coating solutions containing chitosan. Each packaging material was placed in an environment with a temperature of 55°C and a relative humidity of 90% for 10 days, and then was placed at room temperature for 12 hours. The tensile strength and the peeling strength of the film layer of each packaging material, and the antibacterial rates of Staphylococcus aureus, Escherichia coli and Klebsiella pneumoniae were detected according to the foregoing method. The specific results are shown in the following table:

[0078] It can be seen that the pre-oxidized dextran solution and the carboxymethyl chitosan solution are mixed, and then the mixed solution is dropped into a mixed precursor solution containing silver nitrate and copper nitrate to obtain a mixed solution. The mixed solution is reacted in an intermittent microwave environment, and then mixed with deionized water and glycerol to obtain a coating solution containing chitosan. The amino group of the carboxymethyl chitosan and the aldehyde group of the pre-oxidized dextran are covalently cross-linked by forming a Schiff base bond, and the hydroxyl groups exposed by the molecular chain breakage of the pre-oxidized dextran form a dense hydrogen bond network with the carboxymethyl chitosan, enhancing the intermolecular connection and constructing a dense three-dimensional network. At the same time, the aldehyde group of the pre-oxidized dextran reduces metal ions (Ag + , Cu 2+ ) into nano silver particles and nano copper particles under the action of microwave heat effect. On the one hand, the carboxyl group of the carboxymethyl chitosan chelates the nano particles through ionic bonds. On the other hand, the three-dimensional cross-linked network formed by the carboxymethyl chitosan and the pre-oxidized dextran coats the nano silver particles and the nano copper particles, and fills the molecular chain gaps by the nano particles, forming a carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system.

[0079] The carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system is formed by the aforementioned Schiff base covalent bond, the dense hydrogen bond network formed by the hydroxyl groups in the aforementioned pre-oxidized dextran and the carboxymethyl chitosan, the compact three-dimensional network formed, and the filling of the nano silver and nano copper particles to the molecular chain gap, which jointly act on the dispersed stress, improve the mechanical properties of the film layer formed by the coating solution of the composite system, overcome the brittleness defect of the film layer formed by the traditional chitosan coating solution, and improve the flexibility and tear resistance of the film layer by the dextran, and optimize the tensile strength of the film layer.

[0080] Further, the Schiff base bond formed by the amino groups of the carboxymethyl chitosan and the aldehyde groups of the pre-oxidized dextran can replace the original hydrophilic groups, and the nano silver and nano copper particles fill the molecular chain gap of the carboxymethyl chitosan / pre-oxidized dextran, which improves the water resistance of the film layer formed by the coating solution of the composite system, avoids the swelling failure of the film layer in the water-containing environment or humid environment, and further improves the long-term working stability.

[0081] Further, in the aforementioned carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system, the antibacterial performance of the original chitosan is further improved by the nano silver to destroy the cell membrane of gram-negative bacteria or gram-positive bacteria, infect the DNA replication, and the inhibition effect of the nano copper on the mold, which further expands the antibacterial spectrum and improves the antibacterial performance of the film layer, and can effectively inhibit gram-positive bacteria, gram-negative bacteria and mold.

[0082] Further, in the aforementioned carboxymethyl chitosan-pre-oxidized dextran-nano silver / nano copper composite system, the dense crosslinking of carboxymethyl chitosan and pre-oxidized dextran, and the filling effect of nano silver and nano copper particles on the molecular chain gap of carboxymethyl chitosan / pre-oxidized dextran, effectively block the oxygen permeation, further improve the oxygen barrier performance of the film layer; at the same time, combined with the free radical scavenging performance of chitosan and pre-oxidized dextran, and the quenching effect of nano metal ions on free radicals, etc., the film layer is endowed with certain antioxidant performance, which further improves the long-term working stability of the film layer.

[0083] Unless otherwise specified, the percentages used in the present application are mass percentages.

[0084] Finally, it should be pointed out that: the above only describes the preferred embodiments of the present application and is not intended to limit the present application, although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement to some of the technical features. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a chitosan-containing coating liquid, characterized by, The method comprises the following steps: composite modification; The method of the composite modification is that the pre-oxidized dextran solution is added dropwise into the carboxymethyl chitosan solution under stirring, and the pH is adjusted to 7 after the dropwise addition is completed; The mixed precursor solution is continuously added dropwise under stirring, and the mixed solution is uniformly mixed after the dropwise addition is completed; the mixed solution is reacted in an intermittent microwave environment at 57-60°C, and then is placed in an ice bath to obtain a microwave reaction solution; the microwave reaction solution is centrifuged to remove supernatant to obtain a centrifugate; the centrifugate is washed by centrifugation, and then is uniformly dispersed with deionized water and glycerol to prepare a coating solution containing chitosan with a solid content of 1.8-1.9wt%. The mixed precursor solution is an aqueous solution of silver nitrate and copper nitrate.

2. The method for preparing a chitosan-containing coating solution according to claim 1, characterized by, The concentration of the carboxymethyl chitosan solution is 1.2-1.3wt%. The pre-oxidized dextran solution is an aqueous solution of pre-oxidized dextran with an oxidation degree of 27-30%, and the concentration is 1-1.2wt%. The concentration of silver nitrate in the mixed precursor solution is 0.3-0.33mol / L, and the concentration of copper nitrate is 0.1-0.11mol / L.

3. The method for preparing a chitosan-containing coating solution according to claim 1, characterized by, The volume ratio of the pre-oxidized dextran solution to the carboxymethyl chitosan solution is 1:1-1.

1. The volume ratio of the mixed precursor solution to the carboxymethyl chitosan solution is 1:24-25. The added weight of glycerol is 17-19% of the total dry weight of carboxymethyl chitosan and pre-oxidized dextran.

4. The method for preparing a chitosan-containing coating solution according to claim 1, characterized by, The dropwise addition time of the mixed precursor solution is 40-50min. The reaction time of the mixed solution in the intermittent microwave environment is 4-6min at 57-60°C, and the microwave power is 500-550W.

5. The method for preparing a chitosan-containing coating solution according to claim 1, characterized by, The method of the pre-oxidation treatment is that dextran T40 is put into deionized water under room temperature conditions, and then a NaIO4 solution is added dropwise under stirring in a light-proof environment after uniform mixing; the reaction is continued under stirring to obtain a reaction solution; the reaction solution is dialyzed and freeze-dried to prepare pre-oxidized dextran. The weight ratio of dextran T40 to deionized water is 1:20-25.

6. The method for preparing a chitosan-containing coating solution according to claim 5, characterized by, The molar ratio of dextran T40 to NaIO4 in the NaIO4 solution is 1:1.1-1.

2. The concentration of the NaIO4 solution is 0.45-0.5mol / L. The dropwise addition rate of the NaIO4 solution is 0.4-0.6mL / min.

7. The method for preparing a chitosan-containing coating solution according to claim 5, characterized by, The stirring reaction time after the dropwise addition of the NaIO4 solution is completed is 4-5h. The molecular weight cut-off of the dialysis is 12-14KDa, and the dialysis time is 24-30h. The preparation method is prepared by any one of claims 1-7.

8. A coating liquid containing chitosan, characterized by, The coating solution containing chitosan is coated onto the surface of the cellulose base paper, the wet film thickness of the coating is controlled to be 160-170μm, and the coating is dried to prepare a packaging material.

9. Use of the chitosan-containing coating liquid according to claim 8 in a packaging material, characterized in that, In the coating process, the coating speed is controlled to be 12-15m / min.

10. The method for preparing a chitosan-containing coating solution according to claim 9, characterized by, ​ The drying is carried out in a first-stage hot air drying at a temperature of 55-58℃ and a hot air speed of 10-10.5m / s for 40-50s, then in a second-stage hot air drying at a temperature of 63-65℃ and a hot air speed of 8-8.5m / s for 55-60s, and then in a third-stage hot air drying at a temperature of 45-48℃ and a hot air speed of 5-5.5m / s for 45-50s.